Analysis of COVID-19 Prevention and Control Policy Implementation in Islamic Boarding Schools in DKI Jakarta - Wibowo, Dickha Adi; Ariyanti, Fajar (UI Scholars Hub, 2025)
Indonesia, as one of the countries affected by COVID-19, has implemented various efforts to prevent the transmission of COVID-19. One effort that can be implemented is the implementation of COVID-19 prevention protocols. Apart from that, according to the COVID-19 Handling Task Force, Islamic boarding schools are locations with high mobility. This research aims to determine the implementation of policies related to the prevention and control of COVID-19 in Islamic boarding schools in the DKI Jakarta Province. This research used descriptive research with a qualitative approach, with the number of respondents being three Islamic boarding school leaders and students. The results showed that the standards and policies have been implemented but need improvement, especially regarding knowledge related to COVID-19 prevention and control policies in Islamic boarding schools; resources were implemented properly in accordance with the regulations stated in the Decree of the Minister of Health of the Republic of Indonesia Number HK.01.07/Menkes/2322/2020; communication between stakeholders has been carried out well, but the form of communication varies across Islamic boarding schools regarding policy implementation; the attitudes of policy implementers differ in implementing COVID-19 prevention and control policies, especially in the procedures for conducting worship; the implementation of COVID-19 prevention and control measures has been carried out well. The recommendation is that Islamic boarding schools can further improve the implementation of health protocols to prevent future pandemics.